Pope Benedict XVI Democracy and Political Myths - Nedelea, Teodor-Valeriu; Nedelea, Jean (2018)
The present paper starts from the postulate that religion in general, and Christianity in particular, has had and continues to have a significant role in political debates and in the structuring of the public arena. Expounding - in the context of God's return into the life of postsecular society - the vision of the famous theologian Joseph Ratzinger (currently Pope Emeritus Benedict XVI) on democracy and its opponents, this paper also dwells on the manifestations of irrationality in secular religions. Finding its theoretical grounds in myths and utopias, monism of power gives free rein to irrationality in history and ends up in ideology, totalitarianism and crime. Pluralistic democracy, so challenged by enemies from within (relativism, nationalism and communism) as well as without (Islamic terrorism) can be defended and reinvigorated - and Europe alongside it -, Ratzinger states, by restoring Christianity and its values to their rightful place within the public sphere, by means of a fruitful collaboration between reason and faith in the cultural and political life, and by grounding the law in stable, universal ethical principles, which ought to take precedence over any other type of consensus, such as the natural moral law or the dictates of conscience. The central concern of ecclesiastic policy, according to pope Benedict XVI, is defending and promoting freedom, even to the point of martyrdom, by cultivating the dualism of power.
Keywords: Benedict XVI; Europe; Communism; Democracy; Faith; Nationalism; political myths; Reason; liberation theology